Kebijakan Hukum Pidana dalam Penanganan Malpraktik Medis Berdasarkan Perspektif Viktimologi - Qomariyah, Selly Ismi; Tanuwijaya, Fanny; Khanif, Al (Universitas Jember, 2024)
Settlement of medical malpractice cases using litigation is deemed ineffective in terms of benefits both for the health profession as perpetrators and for patients who are victims. Law Number 17 of 2023 concerning health in handling medical malpractice using the principles of restorative justice is expected to be the answer to this problem. Research This study uses a doctrinal legal research method which aims to test the suitability of the principles of restorative justice in legislation with a victimology perspective, which is then updated through reorientation of the suitability of criminal law policy formulations with a victimology perspective in medical malpractice. The results of this research are in principle the current criminal law policy. with the perspective of postmodern victimology in terms of handling medical malpractice, it is compatible. Regarding the issue of criminal liability for perpetrators of medical malpractice, it lies in individuals, namely medical personnel and/or health workers, then corporations, namely health service facilities, but it does not rule out the possibility that criminal liability can be prosecuted against both of them. Even though according to the principles of justice restorative justice has been included in the Health Law but there are no regulations regarding the minimum requirements for suspected medical malpractice that can be resolved using the principles of restorative justice and guidelines for implementing efforts to apply the principles of restorative justice outside of court. Cases of alleged medical malpractice are like icebergs that are more likely to remain untouched than which is already in legal proceedings at both the investigation/investigation and trial levels, while at this stage it is the spearhead of the success of implementing the principles of restorative justice. Therefore, it is necessary to formulate a criminal law policy in the form of material legal rules related to minimum requirements for medical malpractice that can be pursued with restorative justice and formal law related to alternative implementation guidelines. dispute resolution outside of court.Keywords: Medical malpractice, Criminal Law Policy, Victimology, Restorative Justice.